Patterns of Intimate Partner Violence Victimization Among South African Women and Their Relation to Emotional Distress During Pregnancy and Postpartum. Issue 7 (April 2021) - McNaughton Reyes, H. Luz; Maman, Suzanne; Chen, May S.; Groves, Allison K.; Moodley, Dhayendre
Although numerous studies have established a link between intimate partner violence (IPV) victimization and maternal mental health, extant research examining this association has not considered heterogeneity in the forms of IPV that women experience. This is an important gap given that typological perspectives suggest that mental health consequences of IPV victimization may depend on the particular pattern of IPV that is experienced. The current study used latent class analysis to (a) identify and characterize distinct patterns of physical, psychological, and sexual IPV and male controlling behavior in a sample of pregnant South African women ( n = 1, 480) and (b) examine associations between IPV patterns and emotional distress during pregnancy (baseline) and 9 months postpartum (follow-up). Latent class analysis identified a three-class solution wherein the largest class demonstrated a low probability of IPV victimization across all indicators ( nonvictims ; 72% of the sample) and the smallest class demonstrated high probabilities of having experienced moderate and severe forms of IPV victimization as well as male controlling behavior ( multiform severe controlling IPV ; 4% of the sample). A third class ( moderate IPV ) was identified for which there was a high probability of experiencing moderate, but not severe, physical and psychological IPV (24% of the sample). Age, education, cohabitation status, experience of childhood abuse, and forced first sex were associated with class membership. Multiform severe controlling IPV victims reported significantly greater emotional distress than moderate IPV victims and nonvictims at baseline and follow-up. The results contribute to understanding heterogeneity in the patterns of IPV that women experience that may reflect distinct etiological processes and warrant distinct prevention and treatment approaches.